Numerical and Experimental Research on Convergence Angle of Wet Sprayer Nozzle - Chang Su; Yun-hai Cheng (Civil Engineering Journal, 2018)
Shotcrete is a popular support method in construction of both ground projects and underground projects, such as tunnels, subways, slopes and roadway, etc. However, at present researches on the influence of nozzle structure parameters on the performance of concrete injection are insufficient. This research focuses on the influence of various parameters of nozzle structure on the evenness and dust generating, and conducts a systematic study on the flow characteristics of the concrete in the nozzle of wet spraying machinery and the quality control law, through a comprehensive research method combining theoretical analysis, numerical simulation and field tests. On the basis of dynamic analysis of the internal flow field of the nozzle, the mathematical model and numerical model of the internal flow field of the nozzle are establishes. Then the simulation calculation of the flow field of the wet spray nozzle is conducted with the FLUENT® software. The fluid’s contour about velocity and phase volume fraction in the nozzle were obtained. On this basis this paper analyzed each phase’s volume fraction of the mixed fluid in the outlet section. The convergent section of the nozzle is tested in the spray concrete impact force distribution system. The results are in good correspondence with the results of theoretical analysis and numerical simulation, which verifies the validity and reliability of the conclusion of numerical simulation. This paper provides the basis for the optimization of nozzle structure, and the improvement of the sprayed concrete construction quality.